Toxoplasma : - Ajioka, James W. (Horizon Bioscience, 2007)
Ajioka (pathology, University of Cambridge, UK) and Soldati (microbiology and molecular medicine, University of Geneva, Switzerland) collect work by international contributors describing the biological characteristics that make the protozoan parasite Toxoplasma gondii and related apicomplexans the most common and successful group of parasites on earth. Looking at the parasite from both the host and pathogen perspectives, contributors describe the life cycle of Toxoplasma gondii and examine pathogenesis and immunity. They cover both Mendelian and molecular genetics and the latest genomic sequencing results to provide insight on how host-pathogen interactions may shape the parasite's genome organization, population structure, and evolution. They also discuss the core cell biology of the parasite, exploring the relationship between cell cycle, gene expression, nutrient metabolism, and developmental interconversion. The final two sections of the book cover the novel sub-cellular and molecular devices of the parasite cell, the organelles and molecular processes characteristic of apicomplexan parasites, and invasion and occupancy of the host cell. The book will be of interest to researchers working with Toxoplasma and related apicomplexans, such as Plasmodium, Cryptosporidium, and other protozoan parasites.